2009
DOI: 10.1111/j.1471-0307.2008.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional, rheological and sensory characteristics of ice creams with various fat replacers

Abstract: The effects of fat replacers and inulin) on the melting characteristics, overruns, hardness, rheological parameters and sensory attributes of reduced (RF, 60.0 g/kg), low (LF, 40.0 g/kg), and nonfat (NF, 1.0 g/kg) ice creams were investigated. The magnitudes of the melting rates were in the order RF>LF>NF for samples that contained Simplesse® D-100 or inulin, but the reverse order was found for samples with N-Lite D. The nonfat ice creams had lowest overrun values of around 10%. Inulin-containing ice creams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 16 publications
(29 reference statements)
10
81
2
6
Order By: Relevance
“…Similar values were also obtained by Valduga et al (2009) using probiotics, gelatin (collagen), and wheat fiber in the composition of light cheese. Karaca et al (2009) found similar values when evaluating sensorially ice creams with different fat contents.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar values were also obtained by Valduga et al (2009) using probiotics, gelatin (collagen), and wheat fiber in the composition of light cheese. Karaca et al (2009) found similar values when evaluating sensorially ice creams with different fat contents.…”
Section: Resultssupporting
confidence: 59%
“…The following attributes were evaluated: appearance, flavor, aroma, texture and even the willingness to consume the product. We used the affective test with 9-point structured hedonic scale, ranging from 1 (really disliked) to 9 (really liked) for the attributes color, aroma, flavor and texture ANDRAE-NIGHTINGALE et al, 2009;BARIMALAA;OKOROJI, 2009;FAKHOURI et al, 2007;KARACA et al, 2009;MOREIRA et al, 2010;SANTOS et al, 2007SANTOS et al, , 2011.…”
Section: Sensory Analysismentioning
confidence: 99%
“…They reported that dairy low-fat dessert with 5.5 g/100 inulin did not show any significant different acceptability as compared to the dessert with regular fat. As explained by Karaca, Guven, Yasar, Kaya, and Kahyaoglu (2009), a creamy mouth feel is achieved when inulin is used as a fat replacer in dairy products. They interpreted that this might be due to the interaction of inulin with whey protein and caseinate.…”
Section: Sensory Attributesmentioning
confidence: 99%
“…They attributed this subject to the formation of a viscous gel matrix. Karaca et al (2009) argued that the decrease in the firmness of product because of added fat replacer is due to the modifications in the characteristics of fluid surrounding the air cells. Hydrocolloids act as cryoprotectants due to their ability to control water diffusion from and to the ice crystals by steric hindrance and water binding.…”
Section: Physical and Chemical Characteristicsmentioning
confidence: 99%